The Role of Schools in Efforts to Cultivate a Sense of Social Care in Elementary Schools - Nur Aini, Kharisma Risa; Widyasari, Choiriyah (Papanda Publisher, 2025)
The purpose of this study is to explain the role of schools in developing a sense of social care to students and identify obstacles that arise during the implementation of activities. The research method applied is descriptive qualitative with data collection techniques based on documentation, observation, and interviews with principals, class teachers, and 2 students from the high class. The results showed that schools play an important role in instilling the character of social care which is realized through social activities that are carried out regularly and scheduled at MI Muhammadiyah PK Wirogunan which actively involves students and gets support from student guardians. The organized social activities are the dawn alms piggy bank, Friday infaq, and sharing activities with the community. In its implementation, the obstacles experienced were found in the presence of individuals who took items secretly exceeding the specified limit, and the lack of widespread information among the community to find out whether this sharing activity was open to the general public. The obstacles that occur can be constructive input for schools so that activities can take place optimally and in line with the goals set.